Mechanical vibration analysis and computation - Newland, D. E. (Dover Publications, 2006)
Focusing on applications rather than rigorous proofs, this volume is suitable as a text for upper-level undergraduates and graduate students concerned with vibration problems. It also serves as a practical handbook for performing vibration calculations and features extensive appendices and answers to selected problems. 128 figures. 1989 edition.
"An unabridged republication of the third impression (1994) of the work originally published in 1989 by Longman Scientific & Technical"--Title page verso.
Keywords: Vibration.; elektronické knihy; electronic books